Effects of leader safety commitment and perceived organisational support on psychological well-being in chinas higher education: the mediating role of work engagement - Khan, Hanna; Mahomed, Anuar; Mohamed, Rosmah; Qin, L.i.; Jimbun, Joanna (Inderscience Publishers, 2023)
The idea of continuously improving employees’ work engagement by job resources to achieve positive psychological well-being is particularly crucial. This study investigated the impact of mediating effect of leader safety commitment (LSC) and perceived organisational support (POS) on psychological well-being (PWB) among 236 teachers in Chinese public university and examined the mediating effect of work engagement (WE) as a conveyor band that defines LEC, POS and PWB. Structural equation modelling was used to test the hypotheses. The finding showed that POS has positive effect on WE, and WE have positive effect on PWB. On the other hand, WE partially mediated the relationship between POS and PWB, while LSC failed. This study is the first to clarify the importance of perceived organisational support to the mental health of university teachers in the post epidemic period.